2007
DOI: 10.1038/sj.ejcn.1602732
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional modulation of protein metabolism after gastrointestinal surgery

Abstract: Background: The metabolic response to surgery includes alterations in protein metabolism, resulting in a net loss of proteins. Protein hypercatabolism is considered an unavoidable consequence of injury, and an important source of morbidity and mortality. Our purpose was to determine the effect of nutrition on protein metabolism following gastrointestinal surgery, and to elucidate whether postoperative protein loss can be prevented with adequate nutritional support. Methods: Patients who had undergone gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
12
1
1
Order By: Relevance
“…The concentration of 3MeH was measured using high‐performance liquid chromatography according to the laboratory's protocol (SRL Inc.) on the second day of a 3‐day urine collection. Urinary excretion of 3MeH were normalized according to creatinine excretion (3MeH/Cr) to standardize differences in muscle mass …”
Section: Methodsmentioning
confidence: 99%
“…The concentration of 3MeH was measured using high‐performance liquid chromatography according to the laboratory's protocol (SRL Inc.) on the second day of a 3‐day urine collection. Urinary excretion of 3MeH were normalized according to creatinine excretion (3MeH/Cr) to standardize differences in muscle mass …”
Section: Methodsmentioning
confidence: 99%
“…Mikwra et al [34] found that excretion of urinary nitrogen and 3-methylhistidine was significantly reduced during glucose infusion, even at a relatively low rate. Lòpez Hellín et al [35] designed four different parenteral nutritions with increasing glucose, lipid, and amino acid contents during the 7 days following a gastrointestinal operation and found that the higher amino acid content is, the lower the urinary 3-methylhistidine output after the operation is.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extent of surgical intervention often required for radical tumour resection encompasses substantial trauma (Duda et al 2003;Hildebrandt et al 2003;Ló pez Hellín et al 2008), the magnitude of which is proximally correlated with the degree of total serum protein depletion (Tashiro et al 1996;Gibbs et al 1999;Pessaux et al 2003). In addition, intra-operative blood volume loss may compound SA level reduction (Sun et al 2009).…”
Section: Introductionmentioning
confidence: 98%